THE COMMUNITY OF DAWN FIGHTERS: Da'wah, Youth and Rural Muslim Self-Existence - Muhammad Irham; Pipir Romadi; Arya Arwanda (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
This paper tries to analyse the presence of the Community of Dawn Fighters in rural regions, especially in its existence, which is recognised and strongly explores activities and programmers as da'wah activities and the performance of religious theory in rural public spaces. This article will also express the effort and initial exploration of the youth da'wah movement to form a pious and better self. In addition, this article will express the progressivity of young people to be closer to the mosque or mosque, pray at dawn in congregation at the mosque, regularly recite recitations, be persistent in seeking religious knowledge, and preach through the Community of Dawn Fighters. This study also expresses the articulation of the Islamic identity of young people in rural public spaces. Through cognitive observations of participants in the Community of Dawn Keritang Fighters and online interviews (netrography), as well as previous literature sources, this article shows that the form of existence carried out by young people began with: first, these young people carried out early explorations of the socialisation movement and travelled around dawn. Second, young people carry out da'wah activities as a means of existence. Third, these young people publish through attributes and fashion as encouragement in their da'wah. Apart from the progress of existence carried out by young people, what is the strength of this entire movement is the support from various groups and parties, such as the community, ulama, and the local government.